A review on bulk diffusion in metallic solids - Ghorai, Amitava (Diffusion Fundamentals, 2014)
In this paper bulk diffusion techniques in case of metals and alloys will be reviewedwith a special emphasis on resistometric technique. The experiment is restricted only to those metals, which can be made in the form of wire but has the advantage of applying to materials whose suitable radioactive isotopes are not available. A brief introduction along with different diffusion mechanisms with corresponding activation energies, diffusion coefficients, correlation factors, isotope effect, enhancement factor, etc. is also incorporated. Three models for bulk diffusion are also mentioned.